Crimean-Congo Hemorrhagic Fever in Humanized Mice Reveals Glial Cells as Primary Targets of Neurological Infection. (8th May 2017) - Spengler, Jessica R; Kelly Keating, M; McElroy, Anita K; Zivcec, Marko; Coleman-McCray, JoAnn D; Harmon, Jessica R; Bollweg, Brigid C; Goldsmith, Cynthia S; Bergeron, Éric; Keck, James G; Zaki, Sherif R; Nichol, Stuart T; et al.
Abstract : Crimean-Congo hemorrhagic fever in humanized mice indicates a role of glial cell infection in pathogenesis, highlights the importance of additional investigations into neurological disease in human cases, and presents a new model for future studies of pathogenesis and therapeutic screening. Abstract: Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne viral hemorrhagic disease seen exclusively in humans. Central nervous system (CNS) infection and neurological involvement have also been reported in CCHF. In the current study, we inoculated NSG-SGM3 mice engrafted with human hematopoietic CD34 + stem cells with low-passage CCHF virus strains isolated from human patients. In humanized mice, lethal disease develops, characterized by histopathological change in the liver and brain. To date, targets of neurological infection and disease have not been investigated in CCHF. CNS disease in humanized mice was characterized by gliosis, meningitis, and meningoencephalitis, and glial cells were identified as principal targets of infection. Humanized mice represent a novel lethal model for studies of CCHF countermeasures, and CCHF-associated CNS disease. Our data suggest a role for astrocyte dysfunction in neurological disease and identify key regions of infection in the CNS for future investigations of CCHF.